Diseño de un modelo de manejo y abastecimiento de materia prima en la mipyme PikedJeans del sur de Quito - Gordillo Gutiérrez, Marcelo Andrés (2015)
Through this work we have built information and processes that the company has no PikedJeans such as the development of the vision, mission and organization chart, information that we consider it vital circulated to all its employees. By implementing this model we could establish a manual of procedures that facilitated the management of supply and replacement of materials for production, so that should take proper storage and inventory thereof. This model will provide adequate control of inventories and the way how to obtain supplies of materials, will let you know the right time to order and thus how they can cut costs with suppliers and control was also known in what is a waste concern. Through overall objective in our study failed to determine that the company had very basic processes that fell on the owner of the company, which was not good because the company under the guidelines of this person became. The company showed openness to the model as it recognized the benefits generated by the use thereof, such as minimizing idle time production, reduced overtime when the company was supplied prior to their peaks sales, resource optimization, proper storage of materials, encoding the same and decreased costs that this represents. It was determined that the company costs when making this work was not aware of its involvement in production and replacement of materials and the cost of maintaining each unit in inventory and avoid higher costs in a period where production is greater in other.